(untitled) (KYAMC Journal, 2019)
Background: Succinylcholine a depolarizing muscle relaxant with rapid onset, predictable course and short duration of action is associated with myalgia. Objectives: To assess the efficacy of intramuscular injection of diclofenac sodium in preventing succinylcholine-induced myalgia. Materials and Methods: Eighty healthy adults scheduled for elective surgery under general anesthesia were enrolledin a double-blind study and randomly allocated into two groups of forty patients. Patients in Group I (diclofenacgroup) were pretreated with inj. diclofenac 75 mg deep intramuscularly into gluteal region one hour prior to induction of anesthesia, while patients in Group II (saline group) received an equivalent volume of saline inj. in same site. Anesthesia was induced in both groups with fentanyl 1.5 mcg/kg, propofol 2.0 mg/kg and succinylcholine1.5 mg/kg. Postoperative myalgia was assessed 24 hours after induction and graded as nil, mild, moderate, or severe. Results:The demographic data for both groups were comparable (p > 0.05). Postoperative myalgia was recorded at 24 hours after induction in diclofenac group with twelve (30%) patients and 24 (60%) patients in normal saline (control) group respectively (p < 0.05). Conclusion: Prophylactic use of intramuscular injection of diclofenac is effective in the prevention of postoperative myalgia KYAMC Journal Vol. 10, No.-1, April 2019, Page 35-38